Factors affecting the profitability of Nepalese insurance companies - Sah, Laxmi Kumar; Magar, Manisha Rana (Nepalese Journal of Insurance and Social Security, 2021)
This study examines the factors affecting profitability in the context of Nepalese insurance companies. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are liquidity, tangibility, premium growth, firm age and firm size. The study is based on secondary data of 21 insurance companies with 168 observations for the period from 2011/12 to 2018/19. The data is collected from the reports published by Beema Samiti and Annual Reports of selected insurance companies. The regression models are estimated to test the factor affecting the profitability of Nepalese insurance companies. The study showed that firm size has a positive impact on return on assets and return on equity. It indicates that larger firm size leads to increase in return on assets and return on equity. Likewise, premium growth has a positive impact on return on assets and return on equity. It indicates that higher the premium growth, higher would be the return on assets and return on equity. Moreover, firm age has a positive impact on return on assets. It indicates that an increase in firm age leads to increase in return on assets and return on equity. Moreover, assets tangibility has a positive impact on return of assets and return on equity. It means that higher the assets tangibility, the higher would be the return of assets and return on equity. Likewise, there is a negative impact of liquidity ratio on return on assets and return on equity. It means that an increase in liquidity ratio leads to decrease in return on assets and return on equity.